Effects of livelihood diversification on poverty status of rural farming households of Kwara State, Nigeria - Olanike Alaba Ojo; Elizabeth Bukola Olarinoye; Michael Akindele Ojo (Journal of Agriculture and Rural Development in the Tropics and Subtropics, 2024)
Over-dependence on agriculture has failed to provide adequate and sustainable livelihoods for rural households. This study assessed the impact of livelihood diversification on the poverty status of rural farming households in Kwara State, Nigeria. Cross-sectional data were collected from 152 farming households over a period of one year using well-structured questionnaires and interview schedules. Descriptive statistics, Shannon diversity index, Foster, Greer and Thorbecke poverty index, fractional logit and probit regression models were used for analysis. Findings revealed that agriculture-related livelihood activities were still the main livelihood strategy in the area. Although farmers in the study area have a wide variety of livelihood options, the different activities carried out by rural households were very similar such as crop farming, fish farming and palm wine tapping which ranked 1st, 2nd and 3rd, respectively. The main determinants of livelihood diversification were age, gender, household size and farming experience. The main determinants of household poverty were access to credit, gender, age and cooperative membership. The main constraints identified were insufficient funds (own capital) for investment, high transport costs, lack of training to acquire skills, and insufficient credit facilities. Based on these findings, it is recommended that the government should organise training courses on asset accumulation for households through extension services.